Morphometric and Cytogenetic Studies in Mimosa diversipila (Mimosoideae, Leguminosae) and Their Taxonomic and Evolutionary Inferences - Morales, Matias (2014)
Here we describe the morphological variability, chromosome number, and chromosome size in Mimosa diversipila. This speciescomprises two varieties, which are distinguished by the indumentum. However, this character is insufficient for circumscription of theseinfraspecific taxa. Using multivariate techniques, we found that quantitative characters were useful for identification of the varieties, whichalso have a different geographic distribution. Cytogenetic studies revealed that these taxa form a polyploid complex and that the polyploidymay contribute to the morphological variability observed.